2018
DOI: 10.1159/000489317
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy with Primary Implant Reconstruction: Surgical and Oncological Outcome of 435 Breast Cancer Patients

Abstract: Background: This study aimed to examine the incidence of surgical complications associated with nipple-sparing mastectomy (NSM) with primary implant reconstruction, analyze risk factors for early and late surgical complications of NSM, and determine the incidence of local recurrences and the safety of sparing the nipple-areola complex (NAC). Methods: This retrospective cohort study included 435 patients with 441 NSM procedures over a period of 9 years (2004-2012). All surgical complications and the oncological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Many surgeons have tried to develop various incisions in NSM to deliver better cosmetic outcomes (14)(15)(16). Robotassisted nipple-sparing mastectomy (RNSM) is a procedure that uses robotic systems through axillary or lateral incisions, which results in no scars in the overlying skin.…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons have tried to develop various incisions in NSM to deliver better cosmetic outcomes (14)(15)(16). Robotassisted nipple-sparing mastectomy (RNSM) is a procedure that uses robotic systems through axillary or lateral incisions, which results in no scars in the overlying skin.…”
Section: Introductionmentioning
confidence: 99%
“…Most common post-surgery complications were hematoma, occurring in 14.7% of patients of a series, capsular contractures, necrosis [19]. Higher local recurrence ranged from 1-7.3%, [18,27]. Other complications registered have been summarized in (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…From the research performed, 12 articles have been selected for this work, for a total amount of 2859 patients and 3849 NSM, 772 proven procedures of oncologic prophylaxis related to the studies [17][18][19][20][21][22][23][24][25][26][27][28]. The average follow-up varies from 18 to 79 months (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that NAC was a risk factor for early postoperative complications, but the specific relationship between TTS and complications was still unknown. 5 …”
Section: Introductionmentioning
confidence: 99%